THE USE OF SWEAR WORDS IN LIVE SPEED’S YOUTUBE VIDEO: “LOSE THE GAME, SHAVE YOUR EYEBROWS” - lamsahatma; Ambalegin, Ambalegin (BASIS (Bahasa dan Sastra Inggris), 2023)
This descriptive qualitative research analyzed the swear words utteranced by Speed’s in his YouTube video: lose the game, shave your eyebrows. This research aimed to identify types of swear words based on context and which one the frequenly appears. The data source of the research took video from Live Speed’s YouTube channel who played FIFA game with a kid (30 may 2022). This research used observational methode with non-participatory technique for collecting the data. This research used the referential identity method with technique to analyze the data. Based on finding, there were five utterances types of swear words in Live Speed’s video. Those were 1 data of dysphemism, 3 data of idiomatically, 7 data of abusively, 4 data of emphatically, and 13 data of cathartically. The researchers made a conclusion that the cathartically of swearing is the most frequent utteranced by Speed and kid in his video. In other words, all types of swearing were pronounced to express the feeling to gain the attraction of the viewers without insulting anyone.